Measuring the Temporal Stability of Near-Repeat Crime Patterns: A Longitudinal Analysis - Hatten, David (Crime & delinquency, 2021)
This study investigates the temporal stability of identified near-repeat robbery patterns in Newark, New Jersey. With one noteworthy exception, scholars have yet to explore the temporal stability of identified spatiotemporal crime clusters. Furthermore, researchers have yet to measure the near-repeat phenomenon longitudinally. To fill this gap, this study employs a longitudinal design to measure variation in effect size and significance of identified near-repeat crime patterns across 13 “rolling” one-year time periods within a 2-year study period (January 2015-December 2016). Temporal instability was found within two out of six spatiotemporal crime clusters. Results are reported in the form of formalized descriptive statistics and visualizations of temporal trends.